KERJA SAMA SISTER CITY KOTA JAKARTA DENGAN KOTA BEIJING TERKAIT YOUTH EXCHANGE PROGRAM PADA TAHUN 2017-2019 - Muhammad Khalifah (2022)
This study describes the Sister City Cooperation between the City of Jakarta and the City of Beijing, especially regarding the Youth Exchange Program that occurred in 2017-2019. The Sister City cooperation between the City of Jakarta and the City of Beijing has been established for approximately 30 years, during which there have also been many activities related to the agreement that has been agreed in the Memorandum of Understanding (MoU) which contains cooperation agreements in various fields. fields such as youth and sports, urban planning, arts and culture, transportation, tourism, waste management, and the environment. This research focuses on the Youth Exchange Program as a form of cooperation in the field of youth and on the City of Jakarta as the one who absorbs more knowledge and direct and direct assistance that has been provided by the City of Beijing. This study aims to find out the mechanism for implementing the Youth Exchange Program as a result of the Sister City collaboration between the City of Jakarta and the City of Beijing, especially in 2017-2019. This study uses a qualitative descriptive method to obtain data and an in-depth description of the existing phenomena, and the involvement of various elements such as; government and society as evidence of dependence to advance the interests of the region. Then data were collected through interviews and literature as primary and secondary data sources. This study uses the Sister City concept, which is supported by the City Diplomacy concept to see the form of cooperation between the City of Jakarta and the City of Beijing. Until the results of this study explain starting from the mechanism for implementing the Youth Exchange Program participant selection, Youth Exchange Program activities, the obstacles of the Youth Exchange Program, and also the benefits obtained from the Youth Exchange Program for the two cities, especially the City of Jakarta. Keywords: Sister City, Youth Exchange Program, Jakarta, and Beijing.